POSSIBILITIES OF MEMBRANE BIOREACTORS APPLICATION FOR THE CLEANING OF DOMESTIC WATER TREATMENT ON THE CANALIZATIONAL EDUCATIONAL SPIRITS OF UKRAINE: Array - , І. М., Т. О. (Municipal economy of cities. Series: «Economy science», 2018)
The effectiveness of the membrane bioreactor (MBR) in the treatment of wastewater by a biological method is considered. Experimental studies were conducted on a test membrane bioreactor manufactured by Alfa Laval (Denmark). The process of biological treatment of wastewater using a membrane bioreactor makes it possible to intensify the operation of biological treatment facilities due to the lack of facilities for settling drains, increasing the dose of activated sludge to 12–13 g / l, the precipitation process is replaced by filtration, washing the membrane modules can be carried out without emptying the tanks and without withdrawal of modules from tanks. In the process of testing a membrane bioreactor on the basis of a modular unit manufactured by Alfa Laval (Denmark) for purification of domestic wastewater, a cleaning regime was achieved that meets the requirements for discharge. The effectiveness of cleaning in the main indicators was: COD - 93%, BOD5 - 99%, suspended solids - 98.5%, ammonium nitrogen - 98.5%. For nitrates, the efficiency of MBR was 89% after adjusting the reagent dose (40–50 mg / l) and oxygen dose in the nitrification zone (2–3 mg / l). A phosphate efficiency of 98.6% was achieved after the introduction of aluminum sulfate reagent with a dose of 40–50 mg / l. The conducted research allowed us to obtain a stable mode of operation of ICBMs with the provision of an efficient wastewater treatment process. The dependences of the efficiency of wastewater treatment on MBR by major pollutants (COD, BOD5, nitrogen and phosphorus compounds) are given. This allows you to achieve stringent requirements for the discharge of wastewater into water bodies and reduce the cost of treatment by reducing energy consumption. The mechanism of the operation of MBR under conditions of purification of real wastewater is studied, which allows determining the conditions for using MBR in biological wastewater treatment technology. Keywords: purification, membrane, bioreactor, microfiltration, nitrogen, phosphorus, nitrification, denitrification, reagent